Expression of G protein‐coupled oestrogen receptor in melanoma and in pregnancy‐associated melanoma. (20th June 2017) - Fábián, M.; Rencz, F.; Krenács, T.; Brodszky, V.; Hársing, J.; Németh, K.; Balogh, P.; Kárpáti, S.
Abstract: Background: The hormone sensitivity of melanoma and the role of 'classical' oestrogen receptor (ER) α and β in tumour progression have been intensively studied with rather contradictory results. The presence of 'non‐classical' G protein‐coupled oestrogen receptor (GPER) has not been investigated on human melanoma tissues. Objective: To analyse the expression of GPER, ERα and ERβ in pregnancy‐associated (PAM) and in non‐pregnancy‐associated (NPAM) melanomas in correlation with traditional prognostic markers and disease‐free survival (DFS). Methods: Receptor protein levels were tested using immunohistochemistry in 81 formalin‐fixed paraffin‐embedded melanoma tissues. PAMs ( n = 38) were compared with age‐ and Breslow thickness‐matched cases ( n = 43) including non‐pregnant women (NPAM‐W) ( n = 22) and men (NPAM‐M) ( n = 21). The association between receptor expression and DFS was analysed by uni‐ and multivariate Cox proportional hazards regression. Results: G protein‐coupled oestrogen receptor was detected both in PAMs and NPAMs. In 39 of the 41 (95.1%) GPER‐positive melanomas, GPER and ERβ were co‐expressed. GPER/ERβ‐positive melanomas were significantly more common in PAM compared to NPAM ( P = 0.0001) with no significant difference between genders ( P = 0.4383). In PAMs, the distribution of GPER and ERβ was similar (78.4% vs. 81.6%; P = 0.8504), while in NPAM, ERβ was the representative ER (60.5% vs. 27.9%; P = 0.0010) without gender difference (59.1% vs. 61.9%). GPER‐/ERβ‐positive melanomas were associated with lower Breslow thickness, lower mitotic rate and higher presence of peritumoral lymphocyte infiltration (PLI) compared to GPER‐/ERβ‐negative cases ( P = 0.0156, P = 0.0036 and P = 0.0001) predicting a better DFS (HR = 0.785, 95% CI 0.582–1.058). Despite the significantly higher frequency of GPER and ERβ expression in PAM, no significant difference was found in DFS between PAM and NPAM. All but one case failed to show ERα expression. Conclusions: The presence of GPER and its simultaneous expression with ERβ can serve as a new prognostic indicator in a significant subpopulation of melanoma patients.